Respostas

2013-12-15T15:42:33-02:00
(-b+-√Δ)/2a
a)x²-6x+8
(-[-6]+- √-6²-4.1.8)/2.1
(6+- √36-32)/2
(6+- √4)/2
(6+-2)/2
x1=(6+2)/2
x1=8/2
x1=4
x2=(6-2)/2
x2=4/2
x2=2

b)x²-5/6x+1/6
(-[-5/6]+- √-5/6²-4.1.1/6)/2.1
(5/6+- √25/36-2/3)/2
(5/6+- √1/36)/2
(5/6+- 1/6)/2
x1=(5/6+1/6)/2
x1=1/2
x2=(5/6-1/6)/2
x2=(2/3)/2
x2=1/3

c)x²+6x-9
(-6+- √6²-4.1.[-9])/2.1
(-6+- √36-36)/2
(-6+- √0)/2
(-6+-0)/2
x=-3

d)y+3x²+2x+1
-y=3x²+2x+1
(-2+- √2²-4.3.1)/2.3
(-2+- √4-12)/6
(-2+- √-8)/6
Como aqui  Δ<0, não há raiz
4 5 4